The Phenomenon of Islamic Boarding School Traditions Against Modernity: A Case Study of Lirboyo Islamic Boarding School from the Perspective of Mass Media and Social Media - Syah, Syahrudin; Ashari, Zakiah Mohamad (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The phenomenon of modernity, characterized by the acceleration of information technology and the dominance of digital media, has generated profound social, cultural, and epistemological transformations across various spheres of life including within traditional Islamic educational institutions such as pesantren. This article provides an in-depth examination of how Pondok Pesantren Lirboyo in Kediri, East Java, negotiates its traditional identity within the context of digital modernity. The study focuses on the public controversy surrounding the Xpose Uncensored program aired by Trans7 in October 2025, which sparked extensive public reactions. Employing a qualitative approach within the theoretical frameworks of the mediatization of religion and cultural negotiation, this research integrates Critical Discourse Analysis (CDA) of mass media coverage with digital ethnography to trace the dynamics of online discourse and public narratives across platforms such as Twitter/X, Instagram, TikTok, and YouTube. The findings reveal that Pondok Pesantren Lirboyo does not reject modernity outright but rather constructs a model of selective modernization a form of critical engagement with technology and digital media that maintains the core values of Islamic ethics and pesantren traditions. The responses of the pesantren community and santri toward the Trans7 broadcast demonstrate a symbolic awareness aimed at preserving moral authority amid media representation disruptions. Meanwhile, the active use of social media by santri and alumni serves as an instrument of counter-discourse against mainstream media framing, simultaneously strengthening the pesantren’s presence and legitimacy within the digital public sphere. This study concludes that pesantren are now transforming into active cultural agents within the process of mediatization not merely objects of media representation but subjects capable of managing their image, discourse, and identity amidst the flux of global modernity. The phenomenon reinforces the argument that tradition and modernity within Indonesian Islam are not in binary opposition, but exist in a dynamic and productive dialectical relationship.